Real-Time INS/DVL/PS fusion applied to the navigation of Autonomous Underwater Vehicles - Souza, Luiz Felipe; Frutuoso, Adriano; Silva, Daniele Caroline; Barros, Ettore A. De (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2022)
Navigation systems for AUVs are usually constituted by combining data from multiple sensors. Sensory fusion use the measurements and characteristics of different sensors embedded in the vehicle, optimizing the estimates of the vehicle's position. For the sensory fusion, the Kalman filter technique is commonly used. However a critical point of this approach is the tuning and adjustment of some of its parameters, such as measurement and process noise covariance matrices. In this paper, the implementation of an aided inertial navigation system from DVL and PS using the Kalman filter and metrics for filter tuning are discussed.